Transformational diaconia as educative praxis in care within the present poverty-stricken South African context - Tettey, Smith F. K. (HTS teologiese studies, 2020)
This article explores how ministerial and leadership formation could be enabled to adopt transformational diaconia in addressing poverty in South Africa, engaging in ways in which pastoral care and leadership formation can respond to the addressing of poverty. The fact that transformation aims at changing the worldviews, paradigms and approaches to life and problem solving informs the author’s concept of transformational diaconia, which was proposed as an aspect of spiritual leadership capital (SLC), defined as, ‘The inner virtues afforded individuals by their spirituality in formulating their leadership paradigms which contributes to social capital formation for addressing social problems’. Spiritual leadership capital is hereby argued to be a transformative spirituality that can enable an understanding and sustainable responses to poverty and other social problems. This is needed for Africa and particularly for the present day South Africa, seemingly a country with the best infrastructure in Africa; yet its poverty seems pronounced because the dregs of apartheid still lurk in the social fibre, where poor people blame rich people for their plight and vice versa. Bowers Du Toit’s view that ‘[m]ost congregations respond to poverty by providing relief and not empowerment’, re-echoes here. From a mixed-methods research, SLC is a theory recently advanced as a congregational development paradigm and a theology of poverty, which views public theology as an educative praxis that can respond to transformational needs in poverty-related contexts. The authors suggest that for a Church that is responsive to the plight of society, fresh empowerment approaches to address poverty are needed.